The Importance of Packaging in Marketing Traditionally Processed Products in the Women Farming Group “KWT Sumber Rejeki”, Banjar Cengkilung Peguyangan Kangin Denpasar Bali - Astiti, Ni Made Ayu Gemuh Rasa; Semaryani, A. A. Made; Astari, Ni Made Yudi; Parwata, I Kade Wira; Yanti, Gek Dian Dharma (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Packaging has become very important. Packaging no longer functions as a container for wrapping food or beverage products to protect them from dirt, dust, air, impact, and sunlight. It is also a promotional tool to attract buyers' interest. In general, processed livestock products are used for traditional ceremonies. As a tourism area, many domestic and foreign tourists also like Bali's processed livestock products, so the quality of these processed products needs to be improved along with developments in science and technology. Increasing income from the marketing process of processed livestock products will encourage groups of women farmers, who are a source of good fortune, to produce processed traditional food products in greater quantities. Consumers will choose products with attractive packaging compared to plain, simple, and unattractive packaging. The Sumber Rejeki Women's Farmers Group produces traditional food preparations, including Benyah Lab-Lab, Pork Sausage, Chicken Sausage, and Tum. The marketing management process for traditional processed food products produced by partners is very constrained, especially in product packaging, where packaging is crucial in product marketing. The main problem that will be the focus of problem-solving is how to make good packaging that can attract consumers to buy the product.The methods used are presentations and demonstration plots, as well as direct practice in making traditional processed products and packaging processed products produced by partners. It is hoped that the results of this activity will increase the knowledge of the group of women farmers as sources of good fortune and be able to market their products so that the group's income increases. Increasing group income will achieve group prosperity.